2002
DOI: 10.1016/s0969-2126(02)00856-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Analysis of the Kid Toxin Protein from E. coli Plasmid R1

Abstract: We have determined the structure of Kid toxin protein from E. coli plasmid R1 involved in stable plasmid inheritance by postsegregational killing of plasmid-less daughter cells. Kid forms a two-component system with its antagonist, Kis antitoxin. Our 1.4 A crystal structure of Kid reveals a 2-fold symmetric dimer that closely resembles the DNA gyrase-inhibitory toxin protein CcdB from E. coli F plasmid despite the lack of any notable sequence similarity. Analysis of nontoxic mutants of Kid suggests a target in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 34 publications
2
93
0
Order By: Relevance
“…The overall octamer topology of the Rv0301-Rv0300 complex is similar to the N. gonorrhoeae FitAB, 9 S. flexneri VapBC, 30 and R. 4 hexamer when unbound to DNA based on size exclusion chromatography and multiangle light scattering. 26 However, structures of FitAB, S. flexneri VapBC, and the Rv0301-Rv0300 complex have been observed only as octamers bound or unbound to DNA, so these most likely exist as stable octamers in vivo.…”
Section: The Functional Unit Of Rv0301 Toxin Is a Homodimermentioning
confidence: 85%
See 1 more Smart Citation
“…The overall octamer topology of the Rv0301-Rv0300 complex is similar to the N. gonorrhoeae FitAB, 9 S. flexneri VapBC, 30 and R. 4 hexamer when unbound to DNA based on size exclusion chromatography and multiangle light scattering. 26 However, structures of FitAB, S. flexneri VapBC, and the Rv0301-Rv0300 complex have been observed only as octamers bound or unbound to DNA, so these most likely exist as stable octamers in vivo.…”
Section: The Functional Unit Of Rv0301 Toxin Is a Homodimermentioning
confidence: 85%
“…2 The first toxin structure to be determined was the E. coli F plasmid CcdB toxin. 3 The structures of many toxins, antitoxins, and TA complexes have been determined since, including E. coli plasmid R1 Kid toxin, 4 E. coli MazE-MazF TA complex, 5 broad-hostrange low-copy-number plasmid pSM19035 from Streptococcus pyogenes e 2 f 2 TA complex, 6 E. coli YoeB toxin and YefM2-YoeB TA complex, 7 archaeal Pyrococcus horikoshii aRelE-aRelB TA complex, 8 Neisseria gonorrhoeae FitAB TA complex, 9 solution structure of the broad host range low-copy-number plasmid pRK2/RP4 ParD antitoxin, 10 Mycobacterium tuberculosis (Mtb)…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of Kid (PemK) protein has been determined as a homodimer (11,45). Although the structure of MazF has not been determined, Kamada et al (24) have reported the crystal structure of the MazE-MazF complex (MazF 2 -MazE 2 -MazF 2 ), which was formed by two MazF homodimers and one MazE homodimer.…”
Section: Discussionmentioning
confidence: 99%
“…Although CcdB and MazF proteins are structurally related (44,45), their activities are divergent; CcdB inhibits gyrase through binding to its A subunit, although MazF is a ribonuclease. Still key features of how the antitoxin regulates activity of the toxin are paralleled.…”
Section: Structural Similarities Suggest That the Functional Divergenmentioning
confidence: 99%